PECULIARITIES OF WORD FORMATION OF KINSHIP TERMINOLOGY IN THE CHINESE AND KAZAKH LANGUAGES - А.Ж. Мухaмедсaдыковa (Journal of Oriental Studies, 2019)
The purpose of this article is to describe and identify the peculiarities of word formation of kinship terms in the Chinese and Kazakh languages. Research methodology – this scientific study used the basic methods of comparative linguistics, including descriptive, apostolically, as well as structural method. The relevance of the article is the system of word formation of terms of kinship in the Chinese and Kazakh languages, similarities and differences of this system. This article is devoted to the peculiarities of word formation of kinship terms in the Chinese and Kazakh languages. Kinship is a social concept, moreover, a historical-ethnic one, since its development is conditioned not only by universal laws, but also by the way of life, culture, and morality of this or that ethno-collective. But the terms of kinship - these are the words that denote the family relationships be- tween people. They are not only part of the vocabulary of the language, but also the spiritual vocabulary of each language. After all, regardless of the difference between languages and a nation, family ties were always the property of society. Kinship terms are distinguished by their rich history, systemic structure, and also an indispensable role in intercultural communication. Among the Turkic languages, the Kazakh language is considered one of the richest in terms of the number of kinship terms. Chinese is one of the richest languages in the world in terms of kinship terms. This scientific article by the method of concur- rent analysis studies the peculiarities of the word formation of kinship terms in the Chinese and Kazakh languages. Previously, the formation of kinship terms in these languages has not been studied, which in turn indicates the relevance of this topic in the field of Sinology. Key words: Chinese language, Kazakh language, Kinship terms, Word formation, Contrasting analysis.